Theoretical perspectives on CO2 2 separation by ionic liquids: Addressing crucial questions - Massoumilari, Sirin; Velioglu, Sadiye (Elsevier, 2025)
The global population explosion necessitates more natural resources for energy, making it a major factor in climate change. CO2 2 is a leading actor in the greenhouse gas effect, and advancements in CO2 2 capture processes have attracted researchers in recent years. Numerous technologies are practiced for CO2 2 separation. Nevertheless, due to the intricate nature of gases and different process conditions, most of them continue to face challenges. To overcome these challenges, researchers focus on finding or designing innovative materials compatible with various processes. From the discovery of high CO2 2 solubility of ionic liquids (ILs), these unique compounds have rapidly gained popularity for different applications like gas separation. Molecular simulations play a crucial role in supporting researchers in understanding the connection between the properties and chemical structure of newly developed materials as ILs in a time-efficient manner. Despite the growing number of molecular simulation studies, there is a gap in the review papers that effectively highlight the benefits and feasibility of the theoretical approach. Up to date, mostly experimental studies mainly focusing on gas transport mechanisms and the relationship between chemical composition and properties were summarized. Herein, we concentrated on molecular simulation studies investigating the adsorption- and membrane-based CO2 2 separation performance of confined ILs. We systematically addressed prominent questions posed by researchers in each simulation study, demonstrating how to examine confined ILs and interpret the resulting data in relation to gas separation performance. The most pertinent inquiries encompass the influence of ion type (cation or anion) on gas adsorption at the gas-liquid interface and through the confined IL phase, the significance of the confined form of cation or anion in gas transport, the impact of IL thickness on gas separation, and the discernible effects of the material in which ILs are confined. Therefore, we hope to guide researchers in developing innovative membranes or adsorbents by leveraging insights obtained from the answers to these questions derived from molecular simulations of confined ILs.
Keywords: Ionic liquids; Polymer; Adsorption; Membrane technology; 2D nanomaterials; Molecular simulations; Modelling